2020
DOI: 10.1155/2020/1593068
|View full text |Cite
|
Sign up to set email alerts
|

Association of EPAS1 and PPARA Gene Polymorphisms with High-Altitude Headache in Chinese Han Population

Abstract: Background. High-altitude headache (HAH) is the most common complication after high-altitude exposure. Hypoxia-inducible factor- (HIF-) related genes have been confirmed to contribute to high-altitude acclimatization. We aim to investigate a possible association between HIF-related genes and HAH in the Chinese Han population. Methods. In total, 580 healthy Chinese Han volunteers were recruited in Chengdu (500 m) and carried to Lhasa (3700 m) by plane in 2 hours. HAH scores and basic physiological parameters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Initially, EPAS1 attracted widespread attention for its important role in Tibetans' adaptation to hypoxia [ 35 , 36 ]. Subsequently, several studies reported that EPAS1 polymorphisms modified the susceptibility to multiple acute altitude sicknesses when Han Chinese rapidly entered the plateau [ 20 , [37] , [38] , [39] , [40] ]. For example, the rs6756667 A allele reduced the risk of acute high-altitude headache and acute appetite loss [ 38 , 40 ], while the rs13419896 A allele made Han Chinese susceptible to acute cardiorespiratory fitness impairment [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, EPAS1 attracted widespread attention for its important role in Tibetans' adaptation to hypoxia [ 35 , 36 ]. Subsequently, several studies reported that EPAS1 polymorphisms modified the susceptibility to multiple acute altitude sicknesses when Han Chinese rapidly entered the plateau [ 20 , [37] , [38] , [39] , [40] ]. For example, the rs6756667 A allele reduced the risk of acute high-altitude headache and acute appetite loss [ 38 , 40 ], while the rs13419896 A allele made Han Chinese susceptible to acute cardiorespiratory fitness impairment [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several studies reported that EPAS1 polymorphisms modified the susceptibility to multiple acute altitude sicknesses when Han Chinese rapidly entered the plateau [ 20 , [37] , [38] , [39] , [40] ]. For example, the rs6756667 A allele reduced the risk of acute high-altitude headache and acute appetite loss [ 38 , 40 ], while the rs13419896 A allele made Han Chinese susceptible to acute cardiorespiratory fitness impairment [ 37 ]. As the research continues to deepen, researchers also observed that the rs13419896 A allele is a risk factor for premature retinopathy, lung cancer, hepatitis B, and liver cirrhosis [ 21 , [41] , [42] , [43] ].…”
Section: Discussionmentioning
confidence: 99%